2012
DOI: 10.1111/j.1365-313x.2012.05006.x
|View full text |Cite
|
Sign up to set email alerts
|

Autopolyploidy differentially influences body size in plants, but facilitates enhanced accumulation of secondary metabolites, causing increased cytosine methylation

Abstract: SUMMARYWhole genome duplication leads to autopolyploidy and brings about an increase in cell size, concentration of secondary metabolites and enhanced cytosine methylation. The increased cell size offers a positive advantage to polyploids for cell-surface-related activities, but there is a differential response to change in body size across species and taxonomic groups. Although polyploidy has been very extensively studied, having genetic, ecological and evolutionary implications, there is no report that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(106 citation statements)
references
References 41 publications
4
101
0
1
Order By: Relevance
“…Ploidy-induced DNA hypermethylation changes have been reported in Eragrostis curvula (54) and Cymbopogon spp. (17). In contrast, DNA methylation sites were found to be comparable between diploids and autotetraploids in Paspalum sp.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Ploidy-induced DNA hypermethylation changes have been reported in Eragrostis curvula (54) and Cymbopogon spp. (17). In contrast, DNA methylation sites were found to be comparable between diploids and autotetraploids in Paspalum sp.…”
Section: Discussionmentioning
confidence: 76%
“…Biologists have long sought to understand how natural selection enabled neopolyploids to overcome early challenges. Many autopolyploidy systems have been developed for this purpose, such as Arabidopsis (11)(12)(13), potato (14), Elymus elongatus (15), Paspalum (16), and Cymbopogon (17). However, further investigations are still needed to examine the scope and scale of neopolyploids' responses to WGDs.…”
mentioning
confidence: 99%
“…Over the past 2 decades, genomic, epigenetic and cytogenetic analyses have repeatedly validated McClintock's predictions in many allopolyploid systems [for some recent reviews see Hufton and Panopoulou, 2009;Jackson and Chen, 2010;Mayfield et al, 2011;De Smet and Van de Peer, 2012;Heslop-Harrison, 2012;Soltis and Soltis, 2012]. Specifically, polyploidization has been associated with sequence loss [Shaked et al, 2001;Ozkan et al, 2003;Han et al, 2005;Tate et al, 2009], changes in epigenetic marks, such as cytosine methylation [Shaked et al, 2001;Madlung et al, 2005;Lavania et al, 2012], the activation of transposons [Kashkush et al, 2003;Madlung et al, 2005;Chen et al, 2008;Kraitshtein et al, 2010;Petit et al, 2010;Hegarty et al, 2011], and recombination between homoeologous chromosomes [Gaeta and Pires, 2010;Salmon et al, 2010;Szadkowski et al, 2010].…”
Section: Structural Genome Changes During Polyploidizationmentioning
confidence: 99%
“…In unique diploid-autotetraploid paired sets of eight diverse clones of six species of Cymbopogon, it has been reported that polyploidy brings about enhanced accumulation of secondary metabolites in all cases, but exerts differential effects on body size in various species. When changed to tetraploidy, the progenitor diploids requiring longer metabolic steps in production of their secondary metabolites are stressed, and those having shorter metabolite routes better utilize their resources for growth and vigour (Lavania et al 2012).…”
Section: Expression Of Multifoliate Traitmentioning
confidence: 99%